Design Of Web-based Qr-code Absence At The Education Office - Alfiah, Fifit; Yondari, Anisa (Pandawan Sejahtera Indonesia, 2019)
The need for fast and accurate data processing is needed by every government agency. The Education Office is an administrative administrator in the field of education that requires a fast system for processing data. The attendance system at the Tangerang Regency education office is already using a fingerprint. However, there are still many obstacles that arise due to lack of tools, and damage to the tool so that it often uses manual attendance. The research method used is the method of data collection, and the analytical method used is a form of Unified Modeling Language. The results and objectives of this study are the creation of a system that can facilitate employee and attendance managers to be more effective and efficient.